Getting beer during commercials: adverse effects of Ad-Avoidance - Torben Stuehmeier; Tobias Wenzel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2009)
This paper studies the impact of ad-avoidance behavior in media markets. We consider a situation where viewers can avoid advertisement messages. As the media market is a two-sided market, increased ad-avoidance reduces advertisers' value of placing an ad. We contrast two financing regimes, free-to-air and pay-TV. We find that increased avoidance opportunities decrease profits and entry in the free-to-air regime. In contrast, in the pay-TV regime, lower income from advertisements are compensated by higher subscription income leaving profits and the number of channels unaflected. Bypassing advertising messages affects welfare ambiguously.
Keywords: L11; L13; 330; Media Markets; Two-Sided Markets; Ad-avoidance; Fernsehwerbung; Medienverhalten; Medienökonomik; Wohlfahrtseffekt; Theorie